ISLAMIC PRINCIPLES FOR ACHIEVING EDUPRENEURSHIP SUCCESS - Ardhianto, Yusuf; Subiyantoro (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this research is to identify the principles and success criteria of edupreneurship from an Islamic perspective. The research method employed is qualitative-descriptive with a library research approach. The data collection technique used is documentation. The principles of edupreneurship in the Islamic view aim to optimize various potentials to produce both scientific and economic added value that is relevant to the field of Islamic education. Islamic edupreneurship fosters entrepreneurial habits among students, encouraging them to remain creative and innovative, such as writing books according to their interests and fields, or engaging in other activities that can provide economic added value. As a result, it will lead students to a transformation from being consumers to becoming producers. The findings of this research on the principles of edupreneurship from an Islamic perspective include self-confidence, energetic initiative, focus on tasks and results, forward-thinking, leadership qualities, risk-taking, calculated decision-making, communicativeness,reflectiveness, originality, innovation, creativity, flexibility, and wisdom in making policies and decisions.